The Impact of Parents’ Medication Beliefs on Asthma Management - Conn, Kelly M. (Pediatrics, 2007)
BACKGROUND: Previous studies suggest a relationship between parental beliefs about asthma medications and medication adherence. It is not clear how parents’ positive and negative feelings about medications interact to influence medication adherence. OBJECTIVES: The objectives of this study were to describe parents’ perceived need for and concerns about their child’s asthma medications and to assess the weighted impact of these positive and negative beliefs on parent-reported adherence. METHODS: We conducted a cross-sectional survey of parents of children with asthma in southeast Michigan; response rate was 71%. Children with reported use of a preventive asthma medication were included (n = 622). We used a validated Beliefs About Medications Questionnaire (2 subscales: necessity and concern) to assess parents’ positive and negative attitudes about their child’s medications. To measure how parents weigh these beliefs, we also calculated a necessity-concern differential score (difference between necessity and concern subscales). We used a 4-item parent-report scale to measure medication adherence. RESULTS: The majority of children were nonminority. Overall, 72% of parents felt that their child’s asthma medications were necessary, and 30% had strong concerns about the medications. For 77% of parents, necessity scores were higher than concern scores, and for 17%, concern exceeded necessity. Nonminority parents were more likely to have necessity scores exceed concern scores compared with minority parents (79% vs 68%). Mean adherence scores increased as the necessity-concern differential increased. In a multivariate mixed-model regression, a greater necessity-concern differential score and being nonminority predicted better adherence. CONCLUSIONS: These findings confirm a relationship between medication beliefs and adherence among parents of children with asthma. A better understanding of parents’ medication beliefs and their impact on adherence may help clinicians counsel effectively to promote adherence.